Pengaruh Bimbingan Guru Pendidikan Agama Kriten Terhadap Pembentukan Perilaku Siswa Kelas XII SMA Negeri 1 Pahae Julu Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024 - Esra Sitompul; Sandy Ariawan; Rawatri Sitanggang; Lince R.T Simamora; Baginda Sitompul (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
The purpose of this research is to find out how big the influence on the formation of student behavior class XII SMA Negeri 1 Pahae Julu North Tapanuli Regency 2023/2024 Academic Year. The method used in this research is a quantitative research method. The population is all of SMA Negeri 1 Pahae Julu in the 2023/2024 academic year totaling 142 people and a sample of 36 people was determined, namely 25% of the population using random sampling techniques. Data were collected using a positive closed questionnaire of 40 items, namely 24 items for variable X and 16 items for variable Y. The results of data analysis show that there is a positive and significant influence of Christian Religious Education teacher guidance on the formation of student behavior in class XII at SMA Negeri 1 Pahae Julu North Tapanuli Regency 2023/2024 Academic Year. 1) Analysis requirements test: a) positive relationship test obtained a value of rxy =0.581> rtable (a=0,05, df=n-2=34) namely 0,329. b) Significant relationship test obtained a value of tcount= 4.160 > ttable(a=0.05,dk=n-2=34)= 2.042. 2) Influence test: a) Regression equation test, obtained regression equation Y = 24.77 +0.35X. b) Regression coefficient of determination test (r2) = 33.7%. 3) Hypothesis testing using the F test to obtained Fcount > Ftable = (a=0.05, dk numerator k=16, dk denominator=n-2=36-2=34) namely 17,08 > 1.62. Thus Ha means that there is a positive and significant influence of Religious Education teacher guidance on the formation of student behavior in class XII of SMA Negeri 1 Pahae Julu North Tapanuli Regency for the 2023/2024 Academic Year is accepted and H0 is rejected. So from this, it can be seen that the guidance of Christian Religious Education teachers is very necessary because it has an influence on the formation of student behavior. In connection with the results of this study, the authors provides input material for PAK teachers to increase their duties and responsibilities to provide guidance to students so that their behavior is good.